Pusat Kerajinan Tangan Dan Oleh-Oleh Berbasis Ekowisata Di Bagansiapiapi Dengan Pendekatan Arsitektur Melayu Rokan - Apriliana Hidayati Nurdin; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bagansiapiapi is the capital of Rokan Hilir’s district which are occupied by some activities such as economic sector, marine, agriculture, garden, forest, tourism, and service. Looking by social and culture side, Bagansiapiapi has a famous annual event called Bakar Tongkang. This event makes Bagansiapiapi being visited in tourism sector. Tourism activity related with souvenirs necessary. Itwas being reason why Bagansiapiapi need a place to produce Rokan Hilir unique gift. Handcraft and souvenirs center related with ecotourism as a benefited of natural potential from the site. It expected can be a facilities of recreation and education for learn of Malay culture by applying one of the traditional architecture in Riau, that is Malay Rokan Architecture. By using Malay Rokanarchitecture as a approach for the design, then found a concept is Khazanah Arsitektur Melayu Rokan. The base design idea is Rokan Hilir’s original culture (handcraft and souvenirs). Therefore torise up of Rokan Hilir local characteristic using the traditional house from Malay Rokan Architecture. The concept is applied by transforming traditional house of Malay Rokan into the design process. The results of the transformation from the form of patterns and shapes are applied to the design ofHandcraft center and souvenirs that include zoning, mass order, outdoor planning, mass formation, indoor planning and structure.Key words: Handcraft and Souvenirs Center, Ecotoursm, Form Transformation, Malay Rokan Architecture